Analisis Neutrophil-to-Lymphocyte Ratio dan Platelet-to-Lymphocyte Ratio pada Pasien Infark Miokard Akut - Geoffrey Christian Lo; Freddy Ciptono (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: Acute myocardial infarction (AMI) is a clinical manifestation of coronary atherosclerosis involving chronic inflammation. Neutrophilia, lymphopenia, and thrombocytosis due to systemic inflammation can be measured using hematological markers neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR). Previous studies have reported using NLR and PLR to determine the prognosis of cardiovascular disease. Purpose: This study aims to investigate whether NLR and PLR differ in the incidence of AMI, both NSTEMI (non-ST elevation myocardial infarction) and STEMI (ST elevation myocardial infarction), and to evaluate their predictive value. Methods: A cross-sectional study was conducted using complete blood count data from 141 AMI patients treated at Tzu Chi Hospital from 2018 to 2024 upon their arrival at the emergency room. The data were analyzed using SPSS, utilizing the Mann-Whitney test to identify significant differences, and Receiver Operating Characteristic analysis to assess the predictive value and cut-off points for NLR and PLR. Results: There was a statistically significant difference in NLR in the incidence of AMI (p = 0.013) but no statistically significant difference in PLR in the incidence of AMI (p = 0.549). NLR with a cut-off of 4.34 (sensitivity 60.6%, specificity 60%) showed a low predictive value (AUC = 0.622), and PLR with a cut-off of 158.90 (sensitivity 53%, specificity 57.3%) had no predictive value (AUC = 0.529) to distinguish between NSTEMI and STEMI events. Conclusion: The difference in NLR was more significant and had better predictive value than PLR in AMI